2017
DOI: 10.1155/2017/2054940
|View full text |Cite
|
Sign up to set email alerts
|

A PLZT Novel Sensor with Pt Implanted for Biomedical Application: Cardiac Micropulses Detection on Human Skin

Abstract: Advances in sensors for biomedical applications have been a great motivation. In this research, a PLZT (lead lanthanum zirconate titanate) novel sensor with platinum wire implanted in its longitudinal section was developed through of the synthesis process based on powder technology. The raw materials as lead (PbO), lanthanum (La2O3), zircon (ZrO2), and titanium (TiO2) were used in the formation of the chemical composition (62.8% PbO, 4.5% La2O3, 24.2% ZrO2, and 8.5% TiO2). Then, these powders were submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The low K IC values indicate that the synthesized materials are very brittle and sensitive to mechanical flaws. Similarly, low fracture toughness values, determined by the Vickers indentation technique, have been reported in hydroxyapatite ceramics and PLZT sensor materials [39,40]. The sample sintered at 1500°C has slightly lower fracture toughness values than the sample sintered at 1450°C, which indicates that the denser material is even more brittle than the porous one.…”
Section: Density and Mechanical Propertiessupporting
confidence: 52%
“…The low K IC values indicate that the synthesized materials are very brittle and sensitive to mechanical flaws. Similarly, low fracture toughness values, determined by the Vickers indentation technique, have been reported in hydroxyapatite ceramics and PLZT sensor materials [39,40]. The sample sintered at 1500°C has slightly lower fracture toughness values than the sample sintered at 1450°C, which indicates that the denser material is even more brittle than the porous one.…”
Section: Density and Mechanical Propertiessupporting
confidence: 52%
“…The practical cases discussed here are part of the research experienced by Dr. Héctor Herrera Hernández known in the scientific community as DR.3H. Recently, DR.3H and his students & research group are dedicated to their experience in electrochemical impedance knowledge in medical applications as bone replacement or PVDF-based membranes as an appropriate scaffold for skin cell growth [35].…”
Section: àmentioning
confidence: 99%
“…Considering the temperature effect during the synthesis process (Miranda Hernández et al, 2018), it was found that the calcium aluminate material synthesized by an in-situ solid state reaction between Al 2 O 3 and CaCO 3 obtained from snail shells is feasible, but the results show that this material is brittle. However, there are several investigations showing that the incorporation of metallic or ceramic particles into the matrix of the ceramic materials modified their physical properties and mechanical properties, such as hardness, fracture toughness, elastic modulus, and fatigue strength (Naga et al, 2019;Tahaa et al, 2017;Granados et al, 2017;José et al, 2016;Sergejev and Antonov, 2006;Moradkhani et al, 2013;Pramanick, 2015;González-Morán et al, 2017;Shukla et al, 2010;Dapievea et al, 2018). In other works, the effect of silver particles with calcium aluminate was studied and it was found that with silver particles, calcium aluminate has favorable conditions as an endodontic sealer, that presents improved antibiofilm properties with a positive effect on antimicrobial behavior (Almeida et al, 2018).…”
Section: Introductionmentioning
confidence: 99%